Effect of high resistivity soil under high impulse currents - Syed Abdullah, Syarifah; Idris, Nur Farahi; Mohamad Nor, Normiza; Ahmad, Nurul Nadia; Mahmud, Azwan (Institute of Advanced Engineering and Science, 2024)
In this paper, experimental test results of several ground electrodes surrounded with gravelly soil medium subjected to high impulse currents were studied, to investigate the effect of confined soil surround electrodes. Ground resistance measurements were performed at low magnitude of voltage and current, where the results are compared to the impulse characteristics of ground electrodes. This paper shows a significant difference in the RDC values and impulse characteristics of ground electrodes when gravelly soil medium surrounded the ground electrode in comparison to the electrodes installed in natural soil. This indicates that the confined soil around the electrode has a major effect on the performance of ground electrodes, whether at steady state or under high impulse conditions. Equivalent circuit for each tested electrode was developed with personal simulation program with integrated circuit emphasis (PSPICE), where the effect of inductance was seen in the electrodes surrounded with gravelly soil.